PERBANDINGAN RETURN SAHAM PADA PERUSAHAAN PERKEBUNAN BEI DAN BURSA MALAYSIA - Etty Rahayu Jamil; Wirmie Eka Putra; Fitrini Mansur (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2019)
The purpose of this research is to know the difference between the actual return and the expected return of the stock using the CAPM model in plantation sector companies listed on the Indonesia Stock Exchange and Malaysia Stock Exchange during the period 2015-2017. This research is a quantitative study using secondary data in the form of stock closing price data, stock index and interest rates by the Central Bank. The hypothesis test in this study is an independent sample t-test to compare the results of the calculation of returns obtained. Results of this study is (1) There is a significant difference between actual return and expected return on plantation companies listed on the Indonesia Stock Exchange, (2) There is no significant difference between actual return and expected return on plantation companies listed on Bursa Malaysia, and (3) There is a significant difference between stock returns of plantation sector companies listed on the Indonesia Stock Exchange and Malaysia Stock Exchange during the 2015-2017 period. Both Indonesia and Malaysia obtained negative returns during the study period, but Malaysia's value is better than Indonesia. Keywords: Actual Return, CAPM, Expected Return, and Stock Investment.